Maximal strength on different resistance training rowing exercises predicts start phase performance in elite kayakers - Uali, I.; Herrero, A. J.; Garatachea, N.; Marin, P. J.; Alvear-Ordenes, I.; Garcia-Lopez, D. (The Journal of Strength and Conditioning Research, 2012)
This study aimed to examine the relationship existing between maximum strength values in 2 common resistance training row exercises (bilateral bench pull [BBP] and one-arm cable row [OACR]) and short sprint performance in elite kayakers. Ten junior kayakers (5 women and 5 men) were tested on different days for 1 repetition maximum (1RM) and maximal voluntary isometric contraction in both exercises. Moreover, a 12-m sprint kayak was performed in a dew pond to record split times (2, 5, and 10 m), peak velocity, distance completed considering the first 8 strokes, and mean acceleration induced by right blade and left blade strokes. No differences (p > 0.05) were observed when right and left arms were compared in sprint testing or strength testing variables. Maximal strength values in BBP and OACR were significantly correlated with short sprint performance variables, showing the bilateral exercise with slightly stronger correlation coefficients than the unilateral seated row. Moreover, the relationship between strength testing and sprint testing variables is stronger when maximal force is measured through a dynamic approach (1RM) in comparison with an isometric approach. In conclusion, maximal strength in BBP and OACR is a good predictor of the start phase performance in elite sprint kayakers, mainly the 1RM value in BBP.